Effectiveness of bimodal auditory and electrical stimulation in patients with tinnitus: A feasibility study - Spencer, Shikha; Mielczarek, Marzena; Olszewski, Jurek; Sereda, Magdalena; Joossen, Iris; Vermeersch, Hanne; Gilles, Annick; Michiels, Sarah (Frontiers in Neuroscience, 2022)
Background: Tinnitus is a common symptom, affecting about 10–15% of the adult population. When input from the somatosensory system can influence and/or elicit tinnitus, this type of subjective tinnitus is called somatosensory tinnitus. Recently, a new type of bimodal neurostimulation treatment has shown promising results for a specific subgroup within the somatosensory tinnitus population. It is, however, not clear if this bimodal stimulation is also effective in patients with other types of subjective tinnitus. Aim: The aim of this study was to evaluate the feasibility and efficacy of non-invasive bimodal auditory-somatosensory stimulation in reducing tinnitus severity among a general population of people with subjective tinnitus. Methods: Chronic subjective tinnitus patients were recruited from the ENT department of the Antwerp University Hospital. Somatosensory stimulation was delivered by Transcutaneous Electrical Nerve Stimulation (TENS), and it was combined with auditory stimulation via headphones. The therapy comprised six sessions of thirty minutes twice a week for a period of 3 consecutive weeks. Follow up measurements were scheduled 9-12 weeks after the last treatment session. The change of the Tinnitus Functional Index (TFI) score, a questionnaire evaluating tinnitus burden and effects on the quality of life, was the primary outcome measure. Results: Twenty-nine patients were enrolled in the study. A linear mixed-effects model was used to analyze the efficacy of bimodal treatment. The results of this analysis showed a statistically significant (by 6,9 points) decrease in average TFI score at the follow up visit when compared to baseline. The ability to modulate tinnitus did not have an influence on the treatment results. Conclusion: Our study showed that bimodal stimulation is a feasible and safe method of tinnitus treatment. The method might be an effective treatment for some participants with tinnitus, especially those who have accompanying neck/temporomandibular problems, although, the evidence from this trial is quite weak. Additional research is needed towards establishing the optimal treatment protocol, as well as selecting the most appropriate inclusion criteria.